Ischemia Modified Albumin Levels in Diabetes Mellitus Patients with and without Diabetic Retinopathy - Sana Rasheed Chaudhry , Muniza Saeed , Zunnera Rashid Chaudhry , Komal Iqbal , Erum Rashid , Faiza Rasheed (Journal of Islamic International Medical College, 2021)
Objective: To determine and compare the levels of ischemia modified albumin (IMA) in healthy individuals, diabetes without retinopathy, and diabetic having no proliferative and proliferative retinopathy. Study Design: Cross sectional comparative study. Place and Duration of study: Diabetic Clinic, Lahore General Hospital from September 2104 to May 2015. Materials and Methods: Sixty subjects were divided into three groups with 20 subjects in each. Group I was control group, included healthy subject, Group II included diabetics without retinopathy and group III included diabetics with retinopathy which comprised of both diabetics with proliferative and non-proliferative diabetic retinopathy. Indirect method using a 90 % D lens was used to diagnose diabetic retinopathy by a consultantp ophthalmologist. The levels of IMA were measured by a colorimetric albumin cobalt binding assay and the values were presented as absorbance units. Data was analyzed using IBM SPSS version 23. Results: Out of 66 % of diabetics individuals 33% were diabetics without retinopathy and 33 % were diabetics with retinopathy out of which 55% had proliferative diabetic retinopathy (PDR) and 45% had non proliferative diabetic retinopathy (NPDR). Low levels of IMA were seen in 33% of diabetics without retinopathy and significantly higher levels of IMA were seen in 27 % of diabetics with proliferative diabetic retinopathy. Conclusion: We conclude from our study that the levels of IMA raise with the progression of the disease, higher levels of IMA are seen in diabetics with proliferative as compared to non proliferative diabetic retinopathy and as compared to diabetic without retinopathy.